Intervention: Engaging post-foundational political theory requires an 'enmeshed' approach. (November 2022) - Blakey, Joe; Machen, Ruth; Ruez, Derek; Medina García, Paula
Abstract: This intervention argues for renewed engagements with post-foundational political theory (PFPT) within political geography. We feel that post-foundational political geography may be on the cusp of becoming consolidated as a distinct and expansive approach to political geographic scholarship, but we argue that reductionist and binary caricatures of its central distinction between 'politics' and 'the political' must be avoided for it to reach its full potential. To this end, we suggest that 'politics' and 'the political' need to be considered as more 'enmeshed' than they have often been represented. We write as four political geographers and will, each in our own ways, highlight how an 'enmeshed' approach to PFPT can better translate its conceptual interventions into political geographic research whilst facilitating productive encounters with the broader worlds of critical geographic inquiry.